2015
DOI: 10.1097/grf.0000000000000124
|View full text |Cite
|
Sign up to set email alerts
|

New Perspectives on the Normal Vagina and Noninfectious Causes of Discharge

Abstract: An understanding of how the vaginal flora is influenced by hormonal status is crucial in distinguishing normal from abnormal secretions. New studies exploring the vaginal microbiome with culture-independent techniques have led to the discovery of previously uncultivable bacteria on a species level, and have contributed to a better understanding of disease processes including bacterial vaginosis. It is important to note that not all vaginal discharge is abnormal or infectious in etiology, but a thorough evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…This runs counter to current notions about Bacteroides , an anerobic bacteria which is considered a commensal of the gastrointestinal tract and has been implicated in BV [ 73 , 74 ]. However, not all vaginal discharge should be considered abnormal [ 75 , 76 ], and therefore it would not be a contradiction for Bacteroides to be associated with a decreased prevalence of “healthy” vaginal discharge (such as cervical mucous released during ovulation) and an increased prevalence of clinical BV. Distinctions such as these will become increasingly important as the scientific community attempts to attain a more nuanced understanding of connections between the microbiome and true clinical disease.…”
Section: Resultsmentioning
confidence: 99%
“…This runs counter to current notions about Bacteroides , an anerobic bacteria which is considered a commensal of the gastrointestinal tract and has been implicated in BV [ 73 , 74 ]. However, not all vaginal discharge should be considered abnormal [ 75 , 76 ], and therefore it would not be a contradiction for Bacteroides to be associated with a decreased prevalence of “healthy” vaginal discharge (such as cervical mucous released during ovulation) and an increased prevalence of clinical BV. Distinctions such as these will become increasingly important as the scientific community attempts to attain a more nuanced understanding of connections between the microbiome and true clinical disease.…”
Section: Resultsmentioning
confidence: 99%
“… 40 Nevertheless, most instances of vaginal discharge are normal and physiological unless accompanied by odor, discomfort, or pruritus. 44 Misperceptions about the vaginal discharge associated with vaginal progesterone administration for LPS can lead to reluctance on the part of some health care professionals to recommend various vaginally administered progesterones. 45 In the current audit, despite reporting vaginal discharge, most patients stated that they perceived the progesterone vaginal tablet to be comfortable, convenient, and easy to use.…”
Section: Discussionmentioning
confidence: 99%
“…There are differences in the composition of normal bacteria in menopausal women. Estrogen is known to play an important role in glycogen deposits and maturation of vaginal epithelium [13]. Hummelen, et al in 2011 observed that the microbiota in menopausal women was dominated by L. iners and L. vaginalis.…”
Section: Etiopatogenesismentioning
confidence: 99%
“…Meanwhile, normal vaginal flora in peri-menopausal women is dominated by L. gasseri or L. jensenii [13].…”
Section: Etiopatogenesismentioning
confidence: 99%